2011
DOI: 10.1007/s11060-010-0514-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear accelerator-based stereotactic radiosurgery for brainstem metastases: the Dana-Farber/Brigham and Women’s Cancer Center experience

Abstract: To review the safety and efficacy of linear accelerator-based stereotactic radiosurgery (SRS) for brainstem metastases. We reviewed all patients with brain metastases treated with SRS at DF/BWCC from 2001 to 2009 to identify patients who had SRS to a single brainstem metastasis. Overall survival and freedom-from-local failure rates were calculated from the date of SRS using the Kaplan-Meier method. Prognostic factors were evaluated using the log-rank test and Cox proportional hazards model. A total of 24 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…Furthermore, the threshold for toxicity of critical structures such as the optic apparatus also limits the dose that can be safely administered near these areas [7][8][9]. Likewise, while brainstem SRS is commonly used including at our institution [10], the doses tend to be somewhat lower than the doses used in other regions of the brain due to toxicity concerns [10][11][12][13], and there appear to be higher risks of complications with lesion volumes greater than 1 cc [12,13]. While WBRT can be used when lesions are felt less suitable for SRS, local therapy may still be preferable in many cases, since the addition of WBRT has not been associated with a survival advantage in addition to local therapy, and is associated with greater short and longterm side effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the threshold for toxicity of critical structures such as the optic apparatus also limits the dose that can be safely administered near these areas [7][8][9]. Likewise, while brainstem SRS is commonly used including at our institution [10], the doses tend to be somewhat lower than the doses used in other regions of the brain due to toxicity concerns [10][11][12][13], and there appear to be higher risks of complications with lesion volumes greater than 1 cc [12,13]. While WBRT can be used when lesions are felt less suitable for SRS, local therapy may still be preferable in many cases, since the addition of WBRT has not been associated with a survival advantage in addition to local therapy, and is associated with greater short and longterm side effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lorenzoni et al identified that doses above 18 Gy predicted improved overall survival, and Trifiletti et al and Kased et al both demonstrated that doses of 16 Gy and above resulted in improved local control [16, 25, 28]. Other studies did not find marginal dose as an important predictor for local control or overall survival in patients treated with SRS for brainstem metastases [18, 19, 21, 24, 26]. Despite the majority of our patients receiving a lower marginal prescription dose of 15 Gy compared with other studies, local control was 78.6 % at 1 year in our series compared with at least 74 to 88 % in other series.…”
Section: Discussionmentioning
confidence: 99%
“…Hatiboglu et al [1] report that twelve of their patients developed fifteen complications due to LINAC-based SRS with serious neurological deficits occurring in two patients (hemiparesis in one patient and hemiparesis and cranial nerve deficit with hemorrhage in another). Kelly et al [12] assert that two patients acquired RTOG grade three toxicities in response to LINAC based SRS, confusion in one and ataxia in the other. Gamma Knife SRS performed by Koyfman et al [5] yielded no grade three or four toxicities; however, weakness, ataxia, and bleeding were observed in three patients.…”
Section: Reviewmentioning
confidence: 99%